CQ 58:2 – Abstracts. (July 2016) - Unknown
Abstract : Ashley Tauchert 'Diary of a literary schizophrenic, 2014' This is based on a journal I kept during a six‐month stay on an Acute psychiatric ward and then in a rehabilitation clinic. It reviews the circumstances that led to my admission and reflects on my experiences of mental illness in the form of a memoir. The piece is written in a series of undated diary entries which interweave my day‐to‐day life as a psychiatric patient with memories and literary reflections. It opens at the point where I am beginning to emerge from a long period of florid psychosis and ends at the point where I am about to be discharged from hospital. By shifting back and forth between momentary experience and surfacing memory, it offers a detailed account of life on a psychiatric ward alongside the strange and colourful experiences I had while living with psychosis. A.D. Harvey 'Eratometrics?' Literature throws up strange coincidences and statistical groupings. One might take warning from Franco Moretti's Maps, Trees, Graphs : Abstract Models for a Literary History, which demonstrates the futility of relying for one's literary historical data on so‐called standard authorities, but statistical analyses of, for example, poetical allusions to Thomas Chatterton or of imitations and translations of the poems of Ossian turn out to be remarkably suggestive. Perhaps we may term this mode of enquiry Eratometrics . A.D. Harvey 'F.R. Leavis at Armageddon' The harrowing experiences of Cambridge critic F.R. Leavis in the Great War were part of his legend; it was even supposed that he had been gassed while serving in an ambulance unit near the front. This is not likely to have endeared him to colleagues in the English Faculty at Cambridge, who included at least five former officers who had been wounded in action and whose injuries – in two cases permanently and painfully crippling – are detailed in their army personal files, now held in the National Archives at Kew. Pamela Thurschwell 'Bringing Nanda forward, or acting your age in The Awkward Age ' Henry James's 1899 novel The Awkward Age posits the adolescent girl's movement forward into the future as an acute problem for the fin de siècle . The novel's titular pun equates the awkward, individual, in‐between time of adolescence with the awkward, collective, in‐between time of the fin de siècle, leading us both towards the turn‐of‐the‐century 'invention' of the modern adolescent, and towards James's exploration of the culturally constructed nature of age as an identity category. The conflation of individual ages with historical ones is significant; James's novel appeared on the cusp of a new century, at a moment when adolescence was in the process of being consolidated as a modern identity category by medical authorities, educators and psychologists. The novel makes explicit the connection between modernity and adolescence, in ways that foreground its troubling adolescent Nanda Brookenham's 'exposure' to the dangerous world of adult knowledge that surrounds her. Its deploying of technologies such as the telegraph and the photograph, which mediate presence, speed time up, slow it down, and freeze it, posits the adolescent girl as cognate with modernity; both of her time and ahead of it. In the novel, adolescence is an awkward, unnerving presence, and a significant absence: an identity in the process of being formulated, and an age category to come.